PERGESERAN MAKNA PANAI’ BERLANDASKAN GAYA HIDUP DI DESA CARREBBU DUSUN BENTENGE KECAMATAN AWANGPONE KABUPATEN BONE SULAWESI SELATAN - Dewi, Irma Ayu Kartika (Jurnal Ar-Risalah, 2022)
The tradition of Uang Panai' at Bugis weddings is indeed very unique. Uang Panai'  is a mandatory requirement in the Bugis marriage custom. Women's social level as a benchmark for the amount of Panai' given. The tradition of Uang Panai' in the modern era is still being maintained and the amount is getting more fantastic. This is because of the lifestyle that influences it. This study discusses the function and meaning of Uang Panai', as well as the influence of lifestyle in the tradition of Uang Panai'. The method used is a literature review and direct interviews with Bugis community members. The results showed that Uang Panai' originally had a meaning as a sign of respect for the woman who wanted to marry. This happens because the Bugis society does not want women to be considered inferior. With the development of the society, human habits are also affected, including in the implementation of Bugis marriages, determination the amount of Uang Panai' is influenced by the lifestyle of the bride and groom. This shift in meaning in giving Panai' Money has become a challenge for men to fulfill Panai's money in a fantastic amount as a form of fulfilling their lifestyle.